2018
DOI: 10.1097/shk.0000000000001023
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and MR-Proadrenomedullin Combination with SOFA and qSOFA Scores for Sepsis Diagnosis and Prognosis: A Diagnostic Algorithm

Abstract: PCT and MR-proADM test combination represent a good tool in sepsis diagnosis and prognosis suggesting their inclusion in the diagnostic algorithm besides SOFA and qSOFA scores. Furthermore, MR-proADM as marker of organ dysfunction, with a turn around time of about 30 min, has the advantage to be more objective and rapid than SOFA score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 35 publications
5
39
2
4
Order By: Relevance
“…For instance, a patient can have a qSOFA ≥2 in acute conditions other than sepsis (e.g., hypovolemia, severe heart failure, or large pulmonary embolism) [ 24 ]. A recent study showed that to improve sepsis identification, the qSOFA score should be used in combination with laboratory tests such as procalcitonin [ 25 ]. However, measurements of procalcitonin were not routine clinical practice in our institution, especially in the preintervention period.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a patient can have a qSOFA ≥2 in acute conditions other than sepsis (e.g., hypovolemia, severe heart failure, or large pulmonary embolism) [ 24 ]. A recent study showed that to improve sepsis identification, the qSOFA score should be used in combination with laboratory tests such as procalcitonin [ 25 ]. However, measurements of procalcitonin were not routine clinical practice in our institution, especially in the preintervention period.…”
Section: Discussionmentioning
confidence: 99%
“…NLCR was calculated as absolute neutrophil count divided by absolute lymphocyte count [15,17]. We explicitly did not study the value of inflammatory markers that were not routinely measured in our hospital, such as procalcitonin and other newly developed markers such as mid-regional pro-adrenomedullin [28].…”
Section: Candidate Predictorsmentioning
confidence: 99%
“…Besides using vital signs, there have been several attempts to predict the prognosis of patients with infectious conditions using biomarkers like lactate and other inflammatory markers [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. When evaluating the prognostic value of biomarkers, the interest is in the value that can be added to already available clinical information (e.g., history and physical examination) [29].…”
Section: Introductionmentioning
confidence: 99%
“…Auch die Entwicklung von Algorithmen zur Diagnose von Sepsis oder septischem Schock kann z. B. bei Einbeziehung von MR-proADM, SOFA und qSOFA signifikant Überlebende und später Verstorbene unterscheiden [34]. Welche Biomarker dabei erhöht sind, hängt aber auch von den auslösenden Pathogenen ab.…”
Section: Biomarker In Kombinationunclassified